2008
DOI: 10.5694/j.1326-5377.2008.tb01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of primary transmission of multidrug‐resistant tuberculosis in the Western Province of Papua New Guinea

Abstract: Objective: To review patient outcomes and the molecular epidemiology of multidrug‐resistant tuberculosis (MDR‐TB) strains isolated from patients living in the Western Province of Papua New Guinea (PNG) seeking treatment in Australia. Design, setting and participants: Review of all cases of MDR‐TB among people living in the open border region between the Western Province of PNG and the Torres Strait Islands of Australia who presented to health clinics in the region between 2000 and 2006. All cases of suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…This maybe indicate that, compared with risk factors of primary DS-TB, primary MDR-TB more likely happens in the low social group. Previous studies displayed that the extensive transmission of MDR-TB had been indicated by molecular epidemiology and happened in urban and rural areas 3032. However, our findings suggested that transmission range of MDR-TB is more limited than that of DS-TB and perhaps, still confined to the low social group.…”
Section: Discussionmentioning
confidence: 45%
“…This maybe indicate that, compared with risk factors of primary DS-TB, primary MDR-TB more likely happens in the low social group. Previous studies displayed that the extensive transmission of MDR-TB had been indicated by molecular epidemiology and happened in urban and rural areas 3032. However, our findings suggested that transmission range of MDR-TB is more limited than that of DS-TB and perhaps, still confined to the low social group.…”
Section: Discussionmentioning
confidence: 45%
“…Our estimate for the Balimo region is higher than the previous Western Province region incidence estimate of 549 cases per 100 000 people per year . The South Fly District and the provincial capital of Daru have previously been noted for having a high burden of TB, and particularly DR‐TB . A heavy burden of TB cases in the North Fly District has previously been observed, while more recent research described 18 cases of TB from Tabubil, with one of these identified as rifampicin resistant .…”
Section: Discussionmentioning
confidence: 95%
“…Some EIDs threaten public health through pandemics with large-scale mortality (e.g., HIV/AIDS). Others cause smaller outbreaks with high fatality rates or lack effective therapies and vaccines (e.g., Ebola virus, rabies, multi-drug resistant TB) [3,4]. As a group, EIDs and re-emerging diseases cause millions of deaths each year, and some single outbreak events (e.g., SARS) have cost the global economy tens of billions of dollars [5].…”
Section: Introductionmentioning
confidence: 99%